Rendahnya Persepsi Gender Mahasiswa di Malang - Daris Zunaida (LPPM Press, 2016)
The dominant concern of this year was the running concept of gender. Understanding aperson's gender is strongly influenced by the perception of gender. The higher the valueperception of gender, the more likely the persons were to understand it. Therefore, it wasimportant to measure the student perceptions of gender because the lower the genderperceptions of students, the lower students understanding of gender would be. If thathappened, it could be potentially causing violence danger and gender stigma done bythe students. This research was conducted on 532 students in Malang by distributingquestionnaires of student gender perceptions. The questionnaire was the result of thegender perception indicator development covering education, marriage and employment.The results showed that the average score of the respondents' perceptions of genderwas 8.31. This value indicated that the number was quite low because it should be themaximum number, that was 13. This indicated that the average score of students’ genderperceptions was about 63.92%.